Animating truth : documentary and visual culture in the 21st century - Ehrlich, Nea (Edinburgh studies in film and intermediality., 2021)
Animating Truth examines the rise of animated documentary in the 21st century, and addresses how non-photorealistic animation is increasingly used to depict and shape reality.